FLOW-INDUCED TRANSVERSE VIBRATION CHARACTERISTICS OF CANTILEVERED RECTANGULAR AND D-SECTION STRUCTURE FOR ENERGY HARVESTING - Kadir, Kadir; Kiwata, Takahiro; Fernanda, Yolli; Barata, La Ode Ahmad (Universitas Halu Oleo, 2020)
We considered the effect of aspect ratio L/H (where L is span length of a prism, and H is the height of a bluff body normal to the flow direction) on the response amplitude of cantilevered rectangular and D-shaped cross-section prims for energy harvesting. The prism was mounted elastically to a plate spring attached to the ceiling wall with a jig in the test section of the water tunnel. The prism with an aspect ratio of L/H = 2.5 has a small angle amplitude as compared to that with L/H ≥ 5. Increment rate of response amplitude of prisms increased proportionally with the aspect ratio. The D-section prism with an aspect ratio of L/H = 10 has a stable peak amplitude and a large increment rate of response amplitude. Therefore, the D-section prism with L/H = 10 is a more suitable cross-section for energy harvesting from transverse-galloping vibration. By using magnetostricitve material as harvester energy, potential power gained from small side ratio for both prism that is 0.99 and 0.48 volt for D-section and rectangular prisms respectively. Keywords—Flow-induced vibration, Cantilevered prism, Rectangular prism, D-section prism, Aspect ratio